Illusive inclusion – construction of leaders and employees based on nationality. Issue 2 (2014) - Sandra Jönsson; Tuija Muhonen; Christina Scholten; Anders S. Wigerfelt
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to discuss and problematise how leadership and employees, or "employeeship", are constructed within IKEA, a global firm often associated with national identity, and connected to distinct values and a leadership ideal. From a critical management perspective, the authors' intent was to study whether there were hierarchies and polarisations in constructions of leadership and, if so, how they were manifested. Design/methodology/approach – The empirical material consists of 17 interviews with Swedish and non‐Swedish managers at the senior management level and internal documents. Findings – The analysis of the empirical material supports the finding that employees are constructed in superior vs subordinate positions based on beliefs about nationality (ethnicity), wherein the construction of Swedishness is ranked above other nationalities. Based on these constructions, two different dimensions of a leader emerge. The first dimension is one of leading and supporting, which involves personal development and is regarded as something positive. The second dimension involves being a manager, which is perceived as conservative, dreary and unappealing. Originality/value – The study illustrates how leaders in a global firm construct hierarchies and polarisation in the daily work. <ack> <x xml:space="preserve"> Acknowledgements </x> This study was financially supported by VINNOVA, Swedish Governmental Agency for Innovation Systems, Grant P33763‐1. The authors acknowledge that similar sections of this article appear in Jönsson, S., Muhonen, T., Scholten, C. and Wigerfelt, A.S. (2013), "Det finns inget mer svenskt än Ikea", "There is nothing more Swedish than IKEA", Arbetsmarknad & Arbetsliv, Vol 19 No. 2, pp. 27‐40. </ack>